Progressive alterations of left atrial and ventricular volume and strain across chronic kidney disease stages: a speckle tracking echocardiography study - Nguyen, Hoai Thi Thu; Do, Chien Van; Dang, Dieu Thi Vu; Do, Loi Doan; Doan, Linh Huu; Dang, Ha Thi Viet (Frontiers in Cardiovascular Medicine, 2023)
Background: It has been a scarcity of evidence regarding differences in left ventricular (LV) and left atrial (LA) size and strain changes across stages of chronic kidney disease (CKD) and which echocardiographic parameters could be utilized to predict the decline of glomerular filtration rate (GFR).Objectives: This study aimed to evaluate the alterations of LV and LA strain across the reduction of renal function and potential echocardiographic parameters which could be correlated with the GFR decline among patients with CKD.A cross-sectional study was conducted on 169 CKD patients at Bach Mai General Hospital, Hanoi, Vietnam from April to November 2022. Demographic, clinical and laboratory characteristics of patients were collected. Transthoracic echocardiography was performed to measure LV and LA size and strains. Jonckheere-Terpstra test was used to measure the tendency of change. Multivariate linear regression models were performed to find associations between different echocardiographic parameters and renal function reduction.The number of patients with CKD stages 1, 2, 3, 4, and 5 was 21 (12.4%), 28 (16.6%), 27 (16.0%), 22 (13.0%) and 71 (42.0%), respectively. CKD severity was positively associated with LV diastolic and systolic diameters, LV mass, E/e' ratio, and maximal tricuspid regurgitation velocity (TR max), but negatively correlated with the LV global longitudinal strain.Higher severity of CKD stage was associated with higher LA diameter, LA strain, and volume in four and two-chamber views, and lower LA reservoir and conduit function. Left ventricular mass (β = 0.068), ejection fraction (β = 0.112) and left atrial reservoir (β = -0.077) were associated with reduced GFR.Left ventricular mass, ejection fraction, and atrial longitudinal strain by STE should be done at the earlier stages of CKD patients for better follow-up of GFR decline.